Health inequities experienced by people with developmental disabilities - Khanlou, Nazilla; Khan, Attia; Vasquez, Luz Maria; Nunes, F.; Felice, S.; Gateri, Hellen; Srivastava, R.; McMillan, S.; Francis Xavier, J. M. (My University, 2022)
The overall purpose of our project is to develop guidelines and recommendations to guide nurses and other service providers as how to deliver effective quality nursing care for persons with DDs. In this Information Sheet, we report on the findings of a survey conducted with nine young adults with DDs, (with the assistance of their caregivers, as needed) to gather the views and perceptions of these youth about their nursing care experiences. A trained interviewer conducted the surveys via an online video platform (Zoom Pro). The participants were six females and three males, between the ages of 16 and 25 years. The DDs impacting these youth included Autism, ADD, cerebral palsy, cortical visual disabilities, global developmental delay, PDD-NOS along with a gene mutation, Fine-Lubinsky syndrome and Dravet syndrome.
Keywords: developmental disabilities (DDs); nursing care; youth